The Regulatory Improvement of Insurance Law Reform in Order to Pursue the Legal Certainty for the People and the Insurance Company - Wijanto, Wihadi (Global Legal Review, 2023)
The growth of insurance sector in Indonesia so far shows a significant development. The data from the Financial Services Authority (OJK) recorded that in 2020 there were 139 insurance companies had obtained the permits to run their business in Indonesia. This number has been decreasing over the past five years due to the failure of several big insurance companies in managing the customer's insurance premium. For example, Bakrie Life and Bumi Asih Jaya Insurance. The research methods on this dissertation are normative with an empirical support to verify the basic research problem and to regulate an ideal formulation of legal protection for all insurance policyholders against the intentional mismanagement by the insurance companies. The results show that until now the rights of all insurance policyholders are still referring to the Commercial Law ( Trade Law Book ) and the Insurance Law. Both regulations do not specifically regulate the rights of insurance policyholders, especially those related to the investments or funds in the non-state-owned (non-BUMN) insurance companies with the priority of refunding if there is an intentional mismanagement or criminal acts committed by the director of the insurance company. The research concluded that the existing regulations do not provide a legal certainty for the insurance policyholders to get refunds for their deposit funds. This means, there is no legal protection for the insurance policyholders when the above mentioned crime occurs or when a violation occurs, or when there is a reinvestment failure. Therefore, it is recommended that the insurance law regulatory improvements be carried out, specifically those related to: 1) Non-litigation settlement mechanisms such as Arbitration (BANI), 2) Litigation settlement mechanisms including private law suit, force majeure, illegal act, bankruptcy suit against the investment managers, or criminal charges for embezzlement, fraud, or money laundering. In addition, it is necessary to have improvements of the technical provisions POJK No. 06/POJK.07/2022 concerning Consumer and Public Protection in the Financial Services Sector.